Radiation Therapy Combined With Checkpoint Blockade Immunotherapy for Metastatic Undifferentiated Pleomorphic Sarcoma of the Maxillary Sinus With a Complete Response - Guram, Kripa; Nunez, Maria; Einck, John; Mell, Loren K.; Cohen, Ezra; Sanders, P. Dominick; Miyauchi, Sayuri; Weihe, Elizabeth; Kurzrock, Razelle; Boles, Sarah; Sharabi, Andrew B. (Frontiers in Oncology, 2018)
Background: Undifferentiated pleomorphic sarcoma (UPS) of the maxillary sinus is an extremely rare malignancy of the head and neck. Surgery is the mainstay of treatment for UPS; however, proximity to vital structures make it challenging to achieve negative surgical margins. Adjuvant therapy including radiation therapy with or without chemotherapy is generally indicated. Despite advances in multimodality treatment, objective response rates to available therapies and prognosis of metastatic UPS remain dismal. Immunotherapy is now a fourth cornerstone of cancer therapy. In particular, checkpoint blockade immunotherapy is a standard of care for recurrent or metastatic cisplatin refractory head and neck squamous cell carcinoma. Checkpoint blockade immunotherapy is being studied in metastatic sarcoma, including UPS, and while initial results are promising, objective response rates remain below 20%. However, adding radiation therapy to checkpoint blockade immunotherapy has been shown, in both preclinical and retrospective clinical studies, to have combinatorial effects on both local and metastatic disease. Thus, further investigation in warranted into the effects of radiation therapy combined with immunotherapy in head and neck sarcomas. Case presentation: We present a case of metastatic, chemotherapy-refractory, UPS of the maxillary sinus in a 55-year-old male treated with checkpoint blockade immunotherapy combined with palliative radiation and stereotactic radiation which resulted in a complete response. Conclusions: This is the first report to our knowledge of metastatic UPS treated with a combination of radiation and dual agent checkpoint blockade immunotherapy. Further investigation is deserved to study the effects of this combination in patients with metastatic UPS that fails to respond to currently available therapies.